Comparative Analysis of Biological Assets Before and After PSAK 69 on Taufik Hidayat Cattle Farms - Lubis, Jey Bremana Ramadhan; Marbun, Patricia Yosephine Syahrani; Utami, Widya Ayu; Nasirwan, Nasirwan (CV. Rayyan Dwi Bharata, 2024)
This research aims to compare the application of PSAK 69 before and after it’s implementation in Taufik Hidayat’s cattle farming business. The main objective is to compare the accounting treatments related to the recognition, measurement, and presentation of biological assets in financial statement. The research method employed is a qualitative approach using primary and secondary data. Data were obtained through direct interviews with the owner of the cattle farming business Taufik Hidayat, as well as observation and documentation at the research site. Additional, literature review from books, journals, and articles was conducted. The analysis results indicate that before PSAK 69, Taufik Hidayat’s farm used recognition and measurement methods based on historical cost. However, after the implementation of PSAK 69, the farm shifted to the fair value method, which affected the sensitivity of biological assets values to market changes. Disclosure and presentation of biological assets also began to comply with PSAK 69 provisions, although there is still room for improvement. Overall. The implementation of PSAK 69 brings significant changes in the accounting treatment of biological assets in Taufik Hidayat’s cattle farming business.